Implementation of Energy Management System ISO 50001 to Achieve Energy Performance Improvement and Support National Energy Security - Widayati, Endang; Tapparan, Ezrom Max Donnald; R Nurwini, Anggraini (Jurnal Global Ilmiah, 2025)
Efficient energy management is one of the key strategies in supporting national energy security and climate change mitigation. ISO 50001, which has been adopted as SNI ISO 50001, provides a systematic framework for organizations to improve energy performance through continuous improvement. This study aims to analyze the implementation of the ISO 50001-based energy management system (EnMS) in Indonesia, identifying the benefits, success factors, and challenges faced by organizations. The research method uses a direct observation approach at pilot companies during the 2012–2017 period, secondary data analysis through Online Energy Management Reporting (POME), and a literature study of organizations that have implemented or obtained ISO 50001 certification. The results of the study show that the implementation of EnMS has resulted in energy savings of 1,409,476 MWh eq, energy cost savings of more than USD 60 million, and a reduction in CO2 emissions of 938,358 tons by 2017. In 2021, the number of certified companies increased significantly, with total energy savings reaching 11,598,000 MWh eq and CO2 emissions reduced by 4,720,083 tons. In addition to environmental and economic impacts, EnMS also provides added value in the form of increased competitiveness, regulatory compliance, corporate branding, and contributions to national energy conservation targets and Sustainable Development Goals (SDGs). In conclusion, the implementation of ISO 50001 has proven to be an effective sustainable solution that not only improves energy performance but also strengthens national energy security and supports the transition to green energy.